New Observations on the Imperial Reliefs from the Sebasteion at Aphrodisias and the Portraiture of Claudius, Britannicus, and the Young Nero - Pollini, John (Jahrbuch des Deutschen Archäologischen Instituts, 2022)
This article reconsiders the identification of several imperial personages and personifications from the Julio-Claudian Sebasteion at Aphrodisias. Certain of these reliefs also offer insight into the likely reason for the creation of one of Claudius’ portrait types that influenced the hairstyles of his natural son Britannicus and his adopted son Nero. Reevaluated too are portraits in-the-round that have long been attributed to the young Nero but which I show represent instead Britannicus. Even though the epigraphic record proves that many portraits of Britannicus were set up, there has been no agreement about the identification of any of his images. My new observations establish his portrait type, based on numismatic evidence and especially on two little-known sculptural portraits representing him as a child wearing the corona civica. The establishment of Britannicus’ portraiture and revision of the portrait type of the young Nero also lead to new conclusions about the Sebasteion’s problematic ›Two Princes‹ relief.